Deformation and collapse of orthogonal 3D woven composites: quasi-static and impact loading - Turner, Paul (2016)
This thesis presents an experimental and numerical investigation undertaken in order to develop the understanding of the behaviour of orthogonal 3D woven composites under quasi-static tension/compression, out-of-plane bending and dynamic soft and multi-hit ballistic impact load cases. Focus is given to the deformed configuration of samples, and to the initiation and propagation of damage within the material. The damage mitigation properties of the through-the-thickness (TTT) reinforcement are highlighted throughout.